Peranan Partai Politik dalam Melaksanakan Pendidikan Politik (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2017)
Political parties are organized groups and their members have an orientation, values of the same ideals. The aim is to gain political power and to seize political positions, usually by constitutional means to implement their policies. Thus it can be said that political parties are one of the core instructions and modern democracy. Modern democracy relies on a system called representation (repressentif), whether the representation of formal state institutions such as parliament (DPRD / DPR) and representation of community aspirations in party instructions. Political parties function to seek and teach talented persons to actively participate in political activities as party members thus participate in politics. This is an important role in political parties to provide political education for the community.